-7-3z=8+2x

Simple and best practice solution for -7-3z=8+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7-3z=8+2x equation:


Simplifying
-7 + -3z = 8 + 2x

Solving
-7 + -3z = 8 + 2x

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -3z = 8 + 7 + 2x

Combine like terms: -7 + 7 = 0
0 + -3z = 8 + 7 + 2x
-3z = 8 + 7 + 2x

Combine like terms: 8 + 7 = 15
-3z = 15 + 2x

Divide each side by '-3'.
z = -5 + -0.6666666667x

Simplifying
z = -5 + -0.6666666667x

See similar equations:

| x/7=-56 | | -12=-8-2x | | 2/3z=20 | | 3/4c-7=65 | | -99-(-36)= | | y=-1/2+3/2 | | 1(t)=15*4.7 | | 6x+4=10x-12 | | -813=37-17j | | -3.5(-4-9a)=30+43.5 | | 20-240= | | h(x)=2pie | | 2(p-2)=5p-9 | | 5p^2+25p=0 | | 5*r+15/20=4*r-12/4 | | 4y-14=1+y | | 5x+12(3x+49000)=4606000 | | 1/9c=-81 | | 60=-7x-5x | | |x+3|+10=8 | | |x+3|+100=8 | | 2=3-4n+3 | | 6x=7-(4y) | | 1(t)=15*3.2 | | 6(p-4)=4p-46 | | -1+y=-(5y-4) | | 8(-7.9)= | | 13.47+0.09(x+3)=13.97-0.11x | | -10n+5n(n+6)= | | xy+4=z | | 1/3x=-1/2 | | 62x19/31x1/4 |

Equations solver categories